Temporal Dynamics of Salmonella enterica subsp. enterica Serovar Agona Isolates From a Recurrent Multistate Outbreak - Hoffmann, Maria; Miller, John; Melka, David; Allard, Marc W.; Brown, Eric W.; Pettengill, James B. (Frontiers in Microbiology, 2020)
The largest outbreak of Salmonella Agona in the United States occurred in 1998. It affected more than 400 patients and was linked to toasted oat cereal. Ten years later, a similar outbreak occurred with the same outbreak strain linked to the same production facility. In this study, whole-genome sequence (WGS) data from a set of 46 Salmonella Agona including five isolates associated with the 1998 outbreak and 25 isolates associated with the 2008 outbreak were analyzed. From each outbreak one isolate was sequenced on the Pacific Biosciences RS II Sequencer to determine the complete genome sequence. We reconstructed a phylogenetic hypothesis of the samples using a reference-based method for identifying variable sites. Using Single Nucleotide Polymorphism (SNP) analyses, we were able to distinguish and separate Salmonella Agona isolates from both outbreaks with only a few SNP differences between them. The phylogeny illustrates that the 2008 outbreak involves direct descendants from the 1998 outbreak rather than a second independent contamination event. Based on these results, there is evidence supporting the persistence of Salmonella over time in food processing facilities and highlights the need for consistent monitoring and control of organisms in the supply chain to minimize the risk of successive outbreaks.